Desenvolvimento de material balístico baseado em poliestireno e biomassa pós consumo - CARDOSO, Deisylene do Socorro Negrão. (2024)
The search for increasingly resistant materials to provide more security along with sustainable development has gained importance because its development is linked directly to the solution of environmental problems and public safety. Accordingly, the use of recycled raw materials is essential to minimize the cost of production. Thinking about it and the problem of disposal of waste Isopor® which consist of Expanded Polystyrene - EPS, as well as residues from the Acai beneficiation process (.Euterpeoleracea Mart), it developed a ballistic materials helping to reduce the impact environment arising from inadequate disposal. So there was great potential in recycling this combined polymer with gray acai seed, to reinforce the polymer matrix option ballistic materials Ballistic plates EPS + 7% acai ash were made with two different types of thickness of 2.5 - 5.0 cm and with the aim of assessing their ballistic properties, all plates were tested for arms: Rifle CZ 452LKM; IMBEL 380 pistol, revolver barrel short 0,38” and Rifle MD97, with the following calibers of projectiles: 0,22”, 0,38”, 0,380” and 0,223”. The best performances were conjugated ballistic plates of 7.5 cm to 12 cm and the front position to the lateral position of penetration of projectiles, except that the gauge 0,223” across all plates, but suffered deviations in hard composite cores. This result allowed the feasibility of the intended application of the ballistic material for light weapons Level II.